Procurement and inventory logistics optimization of small trade enterprises in Belarus - Kazheunikau, Yauheni (Management and Administration Journal, 2020)
The article describes the state of logistics of small trade enterprises in Belarus, offers an algorithm for optimizing their procurement and inventory, as well as provides an evaluation of results of such optimization for small trade enterprise. The purpose of the study is to improve the procurement and inventory logistics in trade. Research methods: statistical method, analysis and synthesis.